グリーンランドNEEM氷床コアのイオン濃度変動が示す完新世～最終間氷期の環境変動 - 東, 久美子; Wegner, Anna; Hansson, Margareta; 平林, 幹啓; 倉元, 隆之; Twarloh, Birthe; 本山, 秀明; Goto-Azuma, Kumiko; Hirabayashi, Motohiro; Kuramoto, Takayuki; Motoyama, Hideaki (2014)
conference object